Antibacterial effects of levobupivacaine against staphylococcus aureus in a patient-controlled epidural analgesia model: an in vitro experimental study - Gülay Akıncı (Eurasian Journal of Anesthesiology and Intensive Care, 2026)
Aims: Catheter-related infections remain an important complication of epidural analgesia. Local anesthetics may contribute to infection prevention because of their antimicrobial properties. This study aimed to evaluate the antibacterial effects of clinically relevant concentrations of levobupivacaine against Staphylococcus aureus in a simulated patient-controlled epidural analgesia (PCEA) model. Methods: An in vitro experimental PCEA infusion system was established using epidural catheter tubing and 0.2-µm bacterial filters. Four study groups were prepared: 0.125% levobupivacaine + fentanyl, 0.0625% levobupivacaine + fentanyl, fentanyl-only solution, and saline control. Each solution was inoculated with Staphylococcus aureus adjusted to a 0.5 McFarland standard. Solutions were infused continuously for 24 hours. Samples obtained from the filter inlet, outlet, and collection chambers were cultured microbiologically. Scanning electron microscopy was used to evaluate bacterial retention at the filter surface. Results: The saline control group demonstrated the highest bacterial colony counts, whereas levobupivacaine-containing solutions demonstrated significantly lower bacterial colony counts compared with the saline control group (p < 0.05). Increasing levobupivacaine concentration was associated with stronger antibacterial activity. No bacterial growth was detected distal to the epidural bacterial filter in any study group. SEM analysis confirmed bacterial accumulation on the proximal surface of the filter membrane. Conclusion: Levobupivacaine exhibited concentration-dependent antibacterial activity against Staphylococcus aureus in a simulated PCEA model, while epidural bacterial filters effectively prevented bacterial passage under experimental conditions.